Distribusi Zakat Mal dalam Bentuk Kebutuhan Pokok: Telaah Fatwa MUI Sumatera Utara No. 02/Ijtima' Ulama/XIX/2025 - Muhammad Ridwan; Zainal Arifin Purba (CV Global Research Publication, 2026)
Differences in Islamic jurisprudential views concerning the form of zakat al-mal payment constitute a contemporary issue in Islamic law. This study aims to analyze the views of Islamic scholars concerning the form of zakah al-māl payment and the legal basis and considerations underlying Fatwa of the Indonesian Ulema Council (MUI) of North Sumatra Number 02/Ijtima' Ulama/XIX/2025, which permits part of zakah al-māl to be distributed in the form of basic necessities. The study employs a qualitative library research approach with descriptive-analytical and comparative analysis of the fatwa, classical Islamic jurisprudence literature, scholarly opinions, scriptural evidence, legal maxims, and maqāṣid al-sharī‘ah, supported by an interview with a member of the Fatwa Committee of MUI North Sumatra. The findings show that Imam al-Nawawi, Nawawi al-Bantani, and Ibn Qudamah generally do not permit zakat to be paid in a form other than the type of wealth subject to zakat. In contrast, the MUI North Sumatra fatwa permits part of zakah al-māl to be distributed as basic necessities when there is a strong need and clear benefit for the beneficiaries (mustahik). This permissibility is based on a cross-madhhab approach, particularly the opinion of Ali Jum‘ah through Dar al-Ifta’ al-Mishriyyah, the application of relevant Islamic legal maxims, and considerations of public benefit and maqāṣid al-sharī‘ah. The study concludes that distributing zakah al-māl in the form of basic necessities is legally justifiable based on the arguments employed in the fatwa, while not negating the validity of the jurisprudential view requiring zakat to be paid according to the type of wealth subject to zakat.